The Model of Management Quality for Islamic Higher Education: A Case Study at the STIT Al Hikmah Tebing Tinggi - Asari, Hasan; Neliwati, Neliwati; Hasibuan, Ahmad Ibrahim (Universitas Malikussaleh, 2021)
This study aims to analyze the quality management of Islamic higher education at STIT Al Hikmah Tebing Tinggi. The research method used in this research is qualitative research with a phenomenological approach. Based on the results of the study, it was found that planning activities included the activities of the tri dharma tertiary programs, both the development of the vision and mission or the programs carried out based on the results of the evaluation. Meanwhile, the implementation activities include detailing the budget needed to improve the quality of education in the implementation of all forms of academic process activities. The implementation of all work programs that have been arranged according to the time schedule in the semester time period, then compile the details of the needs in carrying out the program that has been planned in the academic process for evaluation purposes. It’s detailed the budget for the need to improve the quality of education for the purpose of implementing all forms of academic process activities. The implementation of all work programs that have been arranged according to the time schedule in the semester time period, arrange the details of the needs in implementing the program that has been planned in the academic process for evaluation purposes. Supervision activities include each academic community that has been determined to provide reports on the progress of program activities that have been carried out in each part of the academic work program that has been announced in the planning.